TLR Signaling-induced CD103-expressing Cells Protect Against Intestinal Inflammation. Issue 3 (March 2015) - Wittmann, Alexandra; Bron, Peter A.; van Swam, Iris I.; Kleerebezem, Michiel; Adam, Patrick; Gronbach, Kerstin; Menz, Sarah; Flade, Isabell; Bender, Annika; Schäfer, Andrea; Korkmaz, Ali Giray; Parusel, Raphael; et al.
Abstract : Background: Toll-like receptor (TLR) expression in patients with inflammatory bowel disease is increased when compared with healthy controls. However, the impact of TLR signaling during inflammatory bowel disease is not fully understood. Methods: In this study, we used a murine model of acute phase inflammation in bone marrow chimeric mice to investigate in which cell type TLR2/4 signal induction is important in preventing intestinal inflammation and how intestinal dendritic cells are influenced. Mice were either fed with wild-type bacteria, able to initiate the TLR2/4 signaling cascade, or with mutant strains with impaired signal induction capacity. Results: The induction of the TLR2/4 signal cascade in epithelial cells resulted in inflammation in bone marrow chimeric mice, whereas induction in hematopoietic cells had an opposed function. Furthermore, feeding of wild-type bacteria prevented disease; however, differing signal induction of bacteria had no effect on lamina propria dendritic cell activation. In contrast, functional TLR2/4 signals resulted in increased frequencies of CD103-expressing lamina propria and mesenteric lymph node dendritic cells, which were able to ameliorate disease. Conclusions: The TLR-mediated amelioration of disease, the increase in CD103-expressing cells, and the beneficial function of TLR signal induction in hematopoietic cells indicate that the increased expression of TLRs in patients with inflammatory bowel disease might result in counterregulation of the host and serve in preventing disease. Abstract : Article first published online 2 February 2015.Supplemental Digital Content is Available in the Text.